What are the complexities surrounding the provision of social infrastructure in South African metropolitan areas considering the Corridors of Freedom plan? - Ngoma, Ralph (University of the Witwatersrand; Faculty of Engineering and the Built Environment, 2016)
The City of Johannesburg has embarked on corridor-development plan to assist in spatially restructuring the spatially fragmented urban form of Johannesburg, which for a long time has disadvantaged poor inhabitants of city which live far from economic centres. The poor seem to be most affected by the inefficient urban form, and that means the city is at the forefront of the public mandate, to redress the past injustices and allow equitable distribution resources. The Corridors of Freedom plan is a corridor development plan aimed at transforming the city through specialised nodal developments along corridors (supported by Bus Rapid Transit (BRT). The research project will focus on the Empire-Perth corridor, particularly on the Westbury precinct. The focus will zero in on the precinct of Westbury, which lies along the corridor. The research project involves assessing the norms and standards of social infrastructure provision in Johannesburg, with a focus on education, health and sport facilities. The assessment will be in correspondence with the Corridors of Freedom plans to provide social infrastructure facilities in Westbury, Johannesburg. Therefore this will be a two-fold assessment of 1) the current norms and standards of the provision of education, health and sport facilities, 2) evaluation of the technical, spatial specifications of the CoF proposed facilities to be provided in Westbury as part of the Strategic Area Framework (SAF).
Case Study: Westbury, Johannesburg
Planning Honours Report 2016, Wits University